Economic threshold in cabbage (Brassica oleracea var, capitata) for chewing foliage insects - DUARTE-G., H. WILLIAM; URRUTIA-P., IVÁN E.; ARIZA-O., RUBÉN D.; CUQUE-Z., JESÚS E. (Revista Colombiana de Entomología, 1998)
Horticulturists of the "Sabana de Bogotá" frequently revert to inadequate use of pesticides lo manage cabbage pest problems In order to contribute with the basic knowledge needed for the implementation of an 1PM program, the economic threshold for foliage feeding insects in this crop was established. The effect of artificial damage on yield was integrated into aspects of control costs and expected market values. Results of defoliation were determined to simulate damage of the external cabbage leaves. Three levels (15, 30, and 45%) of foliar damage during two crop ages: initial (35 to 55 days after transplanting) and final (75 to 95 days after transplanting) were determined. Also, treatments, defoliating the plant two times, one at the initial and one at the final age were realized. Yield losses by head injury were stated as a number of heads per hectare. The experiment was arranged in a randomized block design, factorial arrangement 3 x 3, three replications. To establish control costs, a case study of 10 cabbage’s growers in the experimental area was carried out. A tendency analysis of seasonal patterns in cabbage market prices was made to determine the expected market value of the product. A 12 years series of prices at the "Central de Abastos of Bogotá" was used for this analysis. The final results of this study were that any of the damage levels inflicted during the final age of the crop affected yield more than those carried out during other ages. Models which describe yield loss behavior (Kg/Ha) were established for each age tested. Furthermore, a control cost range, considering the active ingredient, the commercial product, and the kind of application was determined. It was established that considering the extreme control cost, the maximum and minimum expected market value, and the injury effect, no damage of the outer leaves higher than 3,5% of the foliar area can be allowed during the period between 35 and 95 days after transplanting. When the clainage is caused directly to the leaves which form the head. only damage between 150 and 1400 heads per hectare can be tolerated, depending on the control cost and the market value.